Circumferential and Radial Variation in Ring Width in West Himalayan Fir (Abies Pindrow Royle) - Seth, M. K.; Thakur, Madhu; Kapoor, Ira (Indian Forester, 2005)
In West Himalayan fir (Abies pindrow Royle) ring width does not differ significantly among eight cardinal directions. It is negatively and significantly correlated with age. Mean ring width value of juvenile wood is significantly and positively correlated with the mean ring width value of intermediate as well as mature wood. The ring width of individual juvenile wood rings (1-10 from pith) is not correlated with the mean ring width value of mature wood. Based on the results of present investigations it is suggested that any random raidal direction can be used to compare ring width values among straight trees of West Himalayn Fir. A random sample of five juvenile wood rings and four mature wood rings are required to compare the ring width values amongst trees for juvenile wood and mature wood respectively in Abies pindrow Royle.